REDD+ politics in the media: a case study from Brazil - May, P.H.; Calixto, B.; Gebara, M.F. (2011)
The core idea of REDD—reducing emissions from deforestation and forest degradation—is to reward individuals, communities, projects and countries that reduce greenhouse gas (GHG) emissions from forests. Adopted under the UNFCCC (United Nations Framework Convention for Climate Change), the mechanism aims to compensate tropical countries for the carbon benefits that their standing forests (‘avoided emissions’ + ‘carbon stocks’) contribute to mitigating climate change. The objective of the analysis contained in this working paper is to characterise the nature of the discourse related to REDD+ in the Brazilian press from 2005 to 2009, identifying the principal actors who led this debate in the media as well as their positions—as either advocates or adversaries of a particular view on REDD+ —as these positions evolved during this period. This study is part of CIFOR’s Global Comparative Study (GCS) on REDD+, which analyses REDD+ policy, practice and implementation and disseminates lessons learned to a national and global audience. CIFOR’s goal is to generate knowledge and practical tools to support efforts to reduce forest emissions in ways that are effective, efficient and equitable (3Es) and that generate co-benefits such as poverty alleviation and biodiversity conservation (3Es+).